(Study on Extraction of Theobromine from Cacao seed) - Lukman Junaidi; Agus Sudibyo; Hendarti - (Balai Besar Industri Agro, 2007)
Study on Extraction of Theobromine from Cacao seed has been conducted. The study is aimed at evaluating the extraction of theobromine effectiveness using Pavia Method and the modification of Pavia Method. The modification of Pavia Method was based on variation of MgO level and variation of organic solvent used. The variation of MgO level were 6 gr, 3 gr, and 0 gr, and the variation of organic solvent used were etanol, chloroform, and etyl acetate. The result of study showed that there was no significance influence of variation of MgO level on the weight and concentration of theobromine extracted. While the variation of organic solvent used showed significance influence to the weight and concentration of theobromine extracted. The best extraction result was obtained when using ethanol when using ethanol as an organic solvent.